HUBUNGAN MINAT DAN BAKAT DENGAN PARTISIPASI MAHASISWA DEPARTEMEN TEKNIK MESIN DALAM MENGIKUTI PROGRAM KREATIVITAS MAHASISWA (PKM) - Diko Antama; Dori Yuvenda; Waskito Waskito; Purwantono Purwantono (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
ABSTRACT Low student participation in the Student Creativity Program (Program Kreativitas Mahasiswa/PKM) remains a problem at Universitas Negeri Padang, particularly among students of the Department of Mechanical Engineering. Data from the 2025 internal PKM selection at UNP, along with historical data from the past three years, indicate that the representation of Mechanical Engineering students has been fluctuating and tends to be low, thus necessitating an examination of internal factors influencing such participation. This study aims to analyze the relationship between students’ interests and talents and their level of participation in PKM. The research employed a descriptive quantitative method with a correlational approach. The study was conducted through stages including the determination of the population and sample of students from the Mechanical Engineering Education and Mechanical Engineering (Non-Education) programs of the 2022–2024 cohorts using Proportional Stratified Random Sampling, data collection through questionnaire instruments, and data analysis using Pearson correlation tests. The results show that students’ interest, talent, and participation are in the good to high categories. In addition, a strong and significant positive relationship was found between students’ interest and participation, as well as between talent and participation. The main conclusion of this study is that students’ interests and talents play an important role in increasing the participation of Mechanical Engineering students in PKM activities. ABSTRAK Rendahnya partisipasi mahasiswa dalam Program Kreativitas Mahasiswa (PKM) masih menjadi permasalahan di Universitas Negeri Padang, khususnya pada mahasiswa Departemen Teknik Mesin. Data seleksi internal PKM UNP tahun 2025 serta data historis tiga tahun terakhir menunjukkan keterwakilan mahasiswa Teknik Mesin yang fluktuatif dan cenderung rendah, sehingga diperlukan kajian terhadap faktor internal yang memengaruhi partisipasi tersebut. Penelitian ini bertujuan untuk menganalisis hubungan antara minat dan bakat mahasiswa dengan tingkat partisipasi mereka dalam PKM. Metode penelitian yang digunakan adalah kuantitatif deskriptif dengan pendekatan korelasional. Penelitian dilaksanakan melalui tahapan penentuan populasi dan sampel mahasiswa Pendidikan Teknik Mesin dan Teknik Mesin (NK) angkatan 2022–2024 menggunakan teknik Proportional Stratified Random Sampling, pengumpulan data melalui instrumen angket, serta analisis data menggunakan uji korelasi Pearson. Hasil penelitian menunjukkan bahwa minat, bakat, dan partisipasi mahasiswa berada pada kategori baik hingga tinggi. Selain itu, ditemukan hubungan positif yang kuat dan signifikan antara minat dan partisipasi mahasiswa serta antara bakat dan partisipasi mahasiswa. Simpulan utama penelitian ini adalah bahwa minat dan bakat mahasiswa berperan penting dalam meningkatkan partisipasi mahasiswa Teknik Mesin dalam kegiatan PKM.